Application of non-standard methods in the teaching foreign languages in modern school - Bagarad L. A. (Scientific community of students, 2016)
phenomenality and multidimensional nature of non-standard lesson phenomenon, its limitless possibilities when teaching a foreign language at school, its great potential for developing different facets of human nature, organizaton of a creative space for personal development and many other things have led to the fact that teaching science drew attention on creative discoveries of teachers-practitioners. This article presents an analysis of the phenomenon of non-standard lesson in the context of foreign language teaching.
Keywords: нестандартный урок; modern methods; преподавание иностранных языков; современные методики; Сингапурская школа; урок-мюзикл; non-standard lesson; teaching foreign languages; Singapore school; lesson-musical